2007
DOI: 10.7773/cm.v33i1.1226
|View full text |Cite
|
Sign up to set email alerts
|

Nearshore surface temperatures in Antofagasta Bay (Chile) and adjacent upwelling centers

Abstract: IntroducciónLas surgencias costeras derivadas del viento se observan a lo largo de muchas costas del mundo. Son fuertes y persistentes en las principales regiones de surgencia frente a costas de latitudes medias de los mayores continentes (e.g., el Sistema de Humboldt frente a las costas de Chile y Perú), y resulta en el enfriamiento y el enriquecimiento del medio ambiente marino, el cual se caracteriza por altos niveles de productividad y biomasa (Fonseca y Farías 1987, Barbieri et al. 1995.El fuerte transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 15 publications
0
43
0
2
Order By: Relevance
“…Previous studies of topographic eddies include island wake effects (Wolanski and Hamner 1988) and larger headland recirculation features (Penven et al 2000). In general, small-scale headlands in upwelling regions have been neglected on the basis of the expectation that surface wind stress rapidly flushes small bays and precludes the stratification that is typically associated with vertically sheared flow and the potential for retention and accumulation (as in upwelling shadows, Graham and Largier 1997;Marin et al 2001;Pinones et al 2007). We showed that larvae do accumulate in smaller bays in upwelling regions, despite strong surface wind stress and the absence of stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of topographic eddies include island wake effects (Wolanski and Hamner 1988) and larger headland recirculation features (Penven et al 2000). In general, small-scale headlands in upwelling regions have been neglected on the basis of the expectation that surface wind stress rapidly flushes small bays and precludes the stratification that is typically associated with vertically sheared flow and the potential for retention and accumulation (as in upwelling shadows, Graham and Largier 1997;Marin et al 2001;Pinones et al 2007). We showed that larvae do accumulate in smaller bays in upwelling regions, despite strong surface wind stress and the absence of stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Puerto Montt is located close to the southern limit of this species. In Antofagasta Bay, SST is signiWcantly higher than in the surrounding Humboldt Current upwelling system (+2-3°C) due to the bay's particular oceanographic conditions (Piñones et al 2007), and thus SST is comparable to the temperature encountered by C. setosus at its northern distributional limit oV Ecuador (Fischer et al 2009b). Two females (IDs A, B) (inXuence of temperature encountered during larval development) in Antofagasta were maintained individually in Xow-through seawater aquaria (12 l) at ambient temperature »16.0°C, while four females (IDs C, D, E, and F) (inXuence of temperature encountered during embryonic development on larval morphology) were held in 3,200 l Xow-through aquaria (·12 ind./basin) under natural seasonal temperature conditions (up to 10 months; 16-23°C) in Antofagasta.…”
Section: Introductionmentioning
confidence: 99%
“…This appears to be the case of the population in Antofagasta Bay, where the local oceanographic setting promotes circulation and retention of water masses of higher temperature and higher phytoplankton concentration (Piñones et al 2007). Under these local conditions, A. purpuratus display continuous gametogenic activity (Avendaño et al 2008), resembling populations further north.…”
Section: Discussionmentioning
confidence: 99%